Organ-specific differences in endogenous phytohormone and antioxidative responses in potato upon PSTVd infection - Milanović, Jasna; Oklestkova, Jana; Majdandžić, Anamari; Novák, Ondřej; Mihaljević, Snježana (Journal of plant physiology, 2019)
Although structurally simple, viroids can trigger numerous changes in host plants and cause loss of yield in agronomically important crops. This study investigated changes in the endogenous status of phytohormones and antioxidant enzyme activity in Solanum tuberosum cv. Désirée in response to Potato spindle tuber viroid (PSTVd) infection. Phytohormone analysis showed that the content of endogenous jasmonic acid (JA) and its precursor cis-OPDA significantly increased in leaves, while the content of castasterone (CS) increased in both leaves and tubers of systemically infected plants compared to mock-inoculated control plants at 8 weeks post-inoculation. The indole-3-acetic acid content moderately increased only in tubers, while no differences in salicylic acid and abscisic acid content were observed between infected and control plants. Changes in endogenous phytohormone content were associated with upregulated expression of genes involved in the biosynthesis of JA and brassinosteroids, and the metabolism of auxins. Additionally, PSTVd infection provoked overproduction of hydrogen peroxide, which coincided with increased activity of guaiacol peroxidase in leaves and ascorbate peroxidase in potato tubers. The activity of catalase decreased in leaves, while superoxide dismutase activity remained steady regardless of the treatment and organ type. Total ascorbate and glutathione did not change significantly, although a shift towards oxidized forms was observed. Results suggest the existence of organ-specific differences in phytohormone and antioxidative responses in potato upon PSTVd infection. Possible effects of the observed changes on symptom development are discussed.
Keywords: Plant Tubers; kyseliny indoloctové; Chlorophyll; Plant Leaves; Cyclopentanes; Solanum tuberosum; Plant Diseases; Plant Growth Regulators; viroidy; Peroxidases; PSTVd; chlorofyl; cholestanoly; Antioxidants; listy rostlin; cyklopentany; antioxidancia; brassinosteroidy; oxylipiny; regulátory růstu rostlin; Oxylipins; IAA; Viroids; Ascorbate; nemoci rostlin; Brassinosteroids; JA; hlízy rostlin; Indoleacetic Acids; Cholestanols